Legal Responsibility of Travel Services for Consumer Losses - Nainggolan, Ibrahim; Rahimah, Rahimah (Universitas Muhammadiyah Sumatera Utara, 2024)
Organizing travel between the travel agency and its consumers, namely service users, has a legal relationship that creates responsibilities, rights and obligations between the parties. This human relationship in Islam is known as muamalah. One thing that people often do is an agreement. In Arabic, an agreement is 'uquud' which means a (recorded) contract agreement. Legal consequences will arise if business actors do not carry out their obligations properly and consumers will complain if the results received are not in accordance with the agreement at the time of the sale and purchase transaction that was carried out. In a contract or agreement, if the business actor can fulfill his obligations well then the business actor has made an achievement, but if the business actor has been negligent and cannot fulfill his obligations well then a default will arise. Apart from that, business actors or in this case travel agencies can also be subject to criminal penalties, Article 61 UUPK